(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to optimize the strategic direction of PT Krakatau Baja Konstruksi (KBK), a subsidiary of PT Krakatau Steel, by identifying which of its five business lines Manufacturing, Tolling, Fabrication, Importation, and Joint Operation (KSO) should be prioritized to enhance focus, efficiency, and profitability. A mixed-methods approach was used by integrating the Analytical Hierarchy Process (AHP) with thematic analysis and strategic management tools, including SWOT, PESTEL, and Porter’s Five Forces. Qualitative data were collected through Focus Group Discussions (FGDs) and in-depth interviews to establish evaluation criteria, which were then processed through AHP pairwise comparisons to determine the priority ranking of business lines. The results show that Manufacturing is the top-priority business line (23.77%), followed by Importation, Joint Operation, Tolling, and Fabrication. The most influential sub-criterion in the decision-making process is Market Demand and Growth Potential (38.88%), highlighting the significant role of external market dynamics in shaping strategic direction. The developed AHP-based prioritization model provides KBK with a clear, structured framework for effective resource allocation and informed strategic decision-making. It helps management focus on high-impact initiatives to enhance business performance and ensure long-term sustainability. This study offers novelty through its comprehensive integration of AHP with multiple strategic analysis tools in the context of Indonesia’s steel industry an approach that remains rarely applied. The model presented serves as a replicable method for other companies facing similar resource constraints and strategic complexity.